An examination of virtual environment training fidelity on training effectiveness. (2017) - Champney, Roberto K.; Stanney, Kay M.; Milham, Laura; Carroll, Meredith B.; Cohn, Joseph V.
Live training is a vital component of military training. Unfortunately it can be expensive, resource intensive, of limited accessibility or impossible to achieve due to the risks involved. Virtual environment (VEs) training environments can provide trainees with opportunities to practice key skills and work out performance issues in a more cost effective environment, which may lead to more efficient use of live training time. The current study explored this premise by conducting a transfer of training study that examined the question of whether pre-training in low and/or high fidelity VEs can lead to time savings and improved performance in live training environments. In this study, four-person teams received training on a room clearing task either on a low fidelity VE, a high fidelity VE, or no pre-training at all, after receiving familiarisation on the task. After training, all groups transferred to a live shoothouse for 20 test trials. Results suggest that high fidelity VE pre-training may facilitate both faster skill acquisition and better performance in a transfer environment. Although sample size may have prevented the findings from reaching statistical significance, the effects were consistent and of moderate to high effect sizes, suggesting an effect is present.